Evert A. Lindquist, Michael Howlett, Grace Skogstad, Geneviève Tellier and Paul ‘t Hart: Policy Success in Canada. Cases, Lessons, Challenges - Olmeda, Jose A. (Gestión y Análisis de Políticas Públicas, 2024)
Recensión del libro de Evert A. Lindquist, Michael Howlett, Grace Skogstad, Geneviève Tellier y Paul ‘t Hart, Policy Success in Canada: Cases, Lessons, Challenges, Oxford University Press, 2019, 514 pp.